Aerobic oxidative amidation of alkynes using titanium oxide encapsulated cuprous iodide nanoparticles (CuI@TiO2). (22nd June 2018) - Dutta, Pratip Kumar; Dhar, Basabbijayi; Sen, Subhabrata
Abstract : A catalyst consisting of titanium oxide encapsulated cuprous iodide nanoparticles was prepared via a sol–gel method using inexpensive raw materials and was harnessed successfully in the oxidative amidation of alkynes via an environmentally benign and sustainable protocol. Abstract : A catalyst consisting of titanium oxide encapsulated cuprous iodide nanoparticles was prepared via a sol–gel method using inexpensive raw materials and was harnessed successfully in the oxidative amidation of alkynes via an environmentally benign and sustainable protocol. The mechanism of action of this transformation was thoroughly discussed. The robustness of the catalyst was elucidated by the synthesis of diverse analogues of α-ketoarylamide from a variety of electron rich and poor substrates via a simple procedure in moderate to high yields, with no generation of toxic by-products, in good recyclability up to five cycles, under solvent free and aerobic conditions. The chemical nature, morphology and loading of the CuI@TiO2 nanocatalyst were investigated by TEM, SEM, XPS, EDX, powder XRD, BET, TGA and ICP-MS.